Colorectal, Prostate and Pancreas Human Cancers Targeted Bioassay-guided Isolations and Characterization of Chemical Constituents from Tephrosia apollinea - Elsir A. Hassan, Loiy; Adnan Iqbal, Muhammad; S. Dahham, Saad; M. Tabana, Yasser; B. Khadeer Ahamed, Mohamed; M.S. Abdul Majid, Amin (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Cancer is characterized by uncontrolled cell division caused by dysregulation of cell proliferation. Therefore, agents that impair cancer cell proliferation could have potential therapeutic value. Higher plants are considered to be a good source of anticancer agents, and several clinically tested chemotherapeutic agents have been isolated from plants or derived from constituents of plant origin. Methods: In the present study, a prenylated flavone (isoglabratephrin) was isolated from aerial parts of Tephrosia apollinea using a bioassay-guided technique. Chemical structure of the isolated compound was elucidated using spectroscopic techniques (NMR, IR, and LC-MC), elemental analysis and confirmed by using single crystal X-ray analysis. The antiproliferative effect of isoglabratephrin was tested using three human cancer cell lines (prostate (PC3), pancreatic (PANC-1), and colon (HCT-116) and one normal cell line (human fibroblast). Results: Isoglabratephrin displayed selective inhibitory activity against proliferation of PC3 and PANC-1 cells with median inhibitory concentration values of 20.4 and 26.6 μg/ml, respectively. Isoglabratephrin demonstrated proapoptotic features, as it induced chromatin dissolution, nuclear condensation, and fragmentation. It also disrupted the mitochondrial membrane potential in the treated cancer cells. Conclusion: Isoglabratephrin could be a new lead to treat human prostate (PC3) and pancreatic (PANC-1) malignancies.
Keywords: prenylated flavone